(untitled) (Globalization and Business, 2023)
The study showed that reform is effective for young people, whose total duration of participation in the pension scheme is 40 years. In this case, the pension scheme provides a high replacement rate, which is not possible for persons whose participation in the pension scheme is not more than 20 years. An obstacle remains the pressure of the pension system on the State budget. Despite the establishment of a funded pension system, the old-age pension still remains accessible to participants of the scheme, which, as noted by the authors of the reform, by 2030, will have a significant share in the structure of the State budget spending.